Teachers, schools, and society : a brief introduction to education - Sadker, David Miller, 1942-; Zittleman, Karen R. (New York : McGraw-Hill, 2012)
'Combining the brevity of a streamlined Introduction to Education text with the support package of a much more expensive book, the brief edition of Teachers, Schools, and Society encourages experienced instructors to explore their own creativity while ensuring that newer faculty can teach the course with confidence. David Sadker's and Karen Zittleman's lively writing style captures the joys and challenges of teaching. The text stresses the importance of fairness and justice in school and society, focuses on the most crucial topic areas, and integrates the most current issues in education. In addition, the wealth of activities included--from online video observations to portfolio-building exercises--offers a broad range of ways to introduce students to the teaching profession'--
Machine generated contents note: Part I: Teachers and StudentsChapter 1: The Teaching Profession and YouChapter 2: Different Ways of Learning Chapter 3: Teaching Your Diverse StudentsChapter 4: Student Life in School and at HomePart II: FoundationsChapter 5: The Multicultural History of American EducationChapter 6: Philosophy of EducationChapter 7: Financing and Governing America's SchoolsChapter 8: School Law and EthicsPart III: Schools and ClassroomsChapter 9: Reforming America's SchoolsChapter 10: Curriculum, Standards, and TestingChapter 11: Becoming an Effective TeacherText Appendix 1: Reflective Activities and Your PortfolioText Appendix 2: Teacher Competency Exams and Praxis Sample Test QuestionsOnline Appendix A: State Departments of EducationOnline Appendix B: Classroom Objective GuidelinesOnline Appendix C: Q and A Guide to Entering the Teaching ProfessionGlossaryNotesCredits.
Book is accompanied by one CD/diskette, entittled' The teachers, school, and society reader + cd room reader' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references (p. N-1-N-27) and index.
Buku bacaan asas fakulti
Keywords: Teaching; Education -- Study and teaching -- United states; Teachers -- Training of -- United States; EDUCATION / General